Prototypical actions with objects are more easily imagined than atypical actions. Issue 3 (3rd April 2018) - Madan, Christopher R.; Ng, Adrian; Singhal, Anthony
ABSTRACT: Tool use is an important facet of everyday life, though sometimes it is necessary to use tools in ways that do not fit within their typical functions. Here we asked participants to imagine characters using objects based on instructions that fit the prototypical actions for the object or were atypical in a novel object-action imagery task. Atypical action instructions either described sensible, substitute uses of the object, or actions that were bizarre but possible. Participants were better able to imagine the prototypical than atypical actions, but no effect of bizarreness was found. We additionally assessed inter-individual differences in movement imagery ability using two objective tests. Performance in the object-action imagery task correlated with the movement imagery tests, providing a link between motor simulations and mental imagery ability.